Dancing Solutions to Conflict: Field-Tested Somatic Dance for Peace. Issue 3 (2nd July 2016) - Eddy, Martha
ABSTRACT: The ability to creatively resolve conflict supports excellence in communication and fosters a positive classroom/studio climate. Despite the fact that school violence continues to be high, many schools fail to teach conflict management, social-emotional skills, or community building to all educators. This research-based article shares dance strategies that lead toward peaceable behavior using somatic explorations. Dance is used to identify problems from bullying to gun violence and to find solutions. The author's Dynamic Embodiment TM approach to somatic education provides skill-building for stress reduction, enhanced understanding of body cues, and opportunities for the practice of embodied socio-emotional development and conflict resolution. The approach includes a unique progression she has developed to enhance human tolerance, connection, and understanding of issues, feelings, cultures, and values when under duress. Dance improvisation and choreographic methods taught at NYC's 92Y Dance Education Laboratory are shared.